Urinary tract infections in patients with diabetes mellitus: epidemiology, pathogenesis and treatment - Geerlings, Suzanne E. (International journal of antimicrobial agents, 2008)
Patients with diabetes mellitus (DM) have a higher prevalence of asymptomatic bacteriuria (ASB) and incidence of urinary tract infections (UTIs) compared with patients without DM. They also more often have bacteraemia, with the urinary tract as the most common focus for these infections, as well as a higher mortality outside the hospital compared with patients without DM. It appears that the increased prevalence of ASB in diabetic women is not the result of a difference in causative bacteria, as the same virulence factors and resistance to antimicrobials were found in Escherichia coli isolated from the urine of diabetic women with ASB compared with non-diabetic controls. Bacterial growth in vitro is increased after the addition of glucose, however glucosuria is not a risk factor for ASB or for the development of UTIs in vivo. No differences in granulocyte function tests were demonstrated among diabetic women with ASB, non-bacteriuric women and healthy control subjects, but women with both ASB and DM had lower urinary cytokine and leukocyte concentrations than women with ASB without DM. Finally, it was found that E. coli expressing type 1 fimbriae adhere better to uroepithelial cells of women with DM compared with those isolated from women without DM. There are no randomised trials that answer the question as to the optimal duration of treatment for UTIs in diabetic patients. It has been recommended to consider these patients as having a complicated UTI and therefore to treat them for a period of 7–14 days.